Effectiveness of the Al Qahtani method in estimating gestational age in the context of an alleged illegal abortion : a case report - Rijaldi, Ferdy; Yudy, Yudy; Prastyo, Eko; Soedarsono, Nurtami; Yuniastuti, Mindya; Satriyo, Juanda; Auerkari, Elza Ibrahim (Padjadjaran Journal of Dentistry, 2025)
Introduction: Age estimation is crucial in forensic and dental sciences, particularly for determining gestational age in suspected illegal abortion cases. This study highlights the significance of the Al Qahtani method, which focuses on dental development, as a reliable approach for estimating gestational age. Gestational age is commonly assessed through body length, weight, and the maturation of skeletal and dental structures, with radiographs serving as essential tools for evaluating dental development. The aim of this case report is to demonstrate the effectiveness of the Al Qahtani method in estimating gestational age in the context of an alleged illegal abortion. Case report: The body of an unidentified infant was found on the side of the road, wrapped in a piece of white cloth and a brown sarung. It was transported to the hospital’s forensic department for identification. Periapical radiographs were taken of the anterior areas of the teeth, and the Al Qahtani method was employed to determine the age of the deceased infant. The radiographs provided a clear overview of dental maturation, which was essential for accurate age estimation. Conclusion: The Al Qahtani method is recommended as a standard practice in forensic odontology for estimating gestational age in abortion cases. This method contributes significantly to medical treatment, criminal investigations, and legal proceedings, enhancing the accuracy of age determination and supporting both medical and legal contexts.